Can the ACS‐NSQIP surgical risk calculator predict post‐operative complications in patients undergoing flap reconstruction following soft tissue sarcoma resection?. Issue 5 (14th September 2016) - Slump, Jelena; Ferguson, Peter C.; Wunder, Jay S.; Griffin, Anthony; Hoekstra, Harald J.; Bagher, Shaghayegh; Zhong, Toni; Hofer, Stefan O.P.; O'Neill, Anne C.
Abstract : Introduction: The ACS‐NSQIP surgical risk calculator is an open‐access on‐line tool that estimates the risk of adverse post‐operative outcomes for a wide range of surgical procedures. Wide surgical resection of soft tissue sarcoma (STS) often requires complex reconstructive procedures that can be associated with relatively high rates of complications. This study evaluates the ability of this calculator to identify patients with STS at risk for post‐operative complications following flap reconstruction. Methods: Clinical details of 265 patients who underwent flap reconstruction following STS resection were entered into the online calculator. The predicted rates of complications were compared to the observed rates. The calculator model was validated using measures of prediction and discrimination. Results: The mean predicted rate of any complication was 15.35 ± 5.6% which differed significantly from the observed rate of 32.5% ( P = 0.009). The c‐statistic was relatively low at 0.626 indicating poor discrimination between patients who are at risk of complications and those who are not. The Brier's score of 0.242 was significantly different from 0 ( P < 0.001) indicating poor correlation between the predicted and actual probability of complications. Conclusion: The ACS‐NSQIP universal risk calculator did not maintain its predictive value in patients undergoing flap reconstruction following STS resection. J. Surg. Oncol. 2016;114:570–575 . © 2016 Wiley Periodicals, Inc.